Active media : Luminescence of Xe2Cl* upon laser excitation of Cl2 – Xe mixtures in a wide pressure range. (30th November 2020) - Shirokikh, A P; Mamaev, S B
Abstract: The luminescence of Xe2 Cl* excimer upon optical excitation of high-pressure Cl2 – Xe mixtures by XeCl laser pulses (λ = 308 nm) with different energies is investigated. It is shown that small-signal gain of the Xe2 Cl amplifier may reach ≈1.3 × 10 -1 cm -1 in a mixture of Cl2 and Xe with partial pressures of 4 Torr and 9 atm, respectively, and an excitation fluence of 10 26 photons cm -2 s -1 .